Hubungan Antara Akses KB dengan Pemilihan Kontrasepsi Hormonal dan Non Hormonal di Kabupaten Purworejo - Sri Panuntun, Siswanto Agus Wilopo, Lina Kurniawati (Berita Kedokteran Masyarakat (BKM), 2009)
Background: The  report of  2002-2003  Indonesia’s  Demographic and Health Survey  (IDHS)  suggests  that  the prevalence  of  family  planning  in  Indonesia  reach  60   percent with  the  hormonal  contraceptive  increase  by  16 percent  and  the  non hormonal  contraceptive  decrease  by 7  percent. Generally,  the  choice  of contraceptives  is based  on  clear  reasons  to  regulate  the  birth  spacing or  to  limit  births. Factors  determining  the  choice  of  non hormonal contraceptives  include  physical  access  (distance),  economy  (cost),  administration  (service  resource) and  cognitive  accesses  (knowledge).Objective: To  investigate  the  relationship between  contraceptive  accesses and  the  choice of  hormonal and  non hormonal  contraceptives  in Purworejo District.Method:  This was  an observational  study with  a  case  control study  design.Subject: Samples were married women 20-35  years  of  age  that  became  the new  acceptors with  the choice  of non hormonal contraceptives  (IUD) as  the case  (133 women) and of hormonal contraceptives  (pill and  injectable) as  the  control  (133 women)  from  1 January  2004  to  31 December  2004.Data analysis: The  qualitative data  analyses used were univariable,  bivariable and multivariable. Statistical  test used  chi-square  and  logistic  regression.Results: The  bivariable  and multivariable  analyses  showed  that  there was  a  relationship  between  family planning demand  and  the  choice of  non hormonal  contraceptives. Respondent  residing  far  from  family  planning services  tended  to choose non hormonal contraceptives with a chance of 1.9  times higher  (OR=9.5;CI95%=1.16-3.19). The variable  that had  the greatest chance  to  influence  respondents  to choose non hormonal contraceptives was cost  that was  7.5  times  (OR=7.5; CI  95%  =  2.60-21.87). The  respondents  that  utilized  private  facilities tended  to  choose  non  hormonal  contraceptives.Conclusion: Respondents with  family  planning  demand  to  limit  births were  likely  to  choose  non  hormonal contraceptives. Other  factors  affecting  the  choice  of  non hormonal  contraceptives were  income.Keywords:  family  planning  accesses,  family  planning  demand,  choice  of   hormonal  and  non  hormonalcontraceptives,  case  control